Peripheral refraction with dominant design multifocal contact lenses in young myopes - Ferreira, Daniela Lopes (2013)
Purpose: The purpose of this study was to show the potential of a commercial center-distance multifocal soft contact lens to induce relative peripheral myopic defocus in myopic eyes. Methods: Twenty-eight myopic right eyes from 28 patients (mean age: 22.0 ± 2.0 years) were evaluated. The measurements of axial and off-axis refraction were made using a Grand-Seiko WAM-5500 open-field autorefractometer without lens and with multifocal contact lenses (Proclear Multifocal D® Design) of +2.00 D and +3.00 D add power applied randomly. Central mean spherical equivalent refraction was −2.24 ± 1.33 D. Ocular refraction was measured at center and at eccentricities between 35◦ nasal and 35◦ temporal (in 5◦ steps). Results: Baseline relative peripheral refractive error (RPRE) as spherical equivalent (M) was −0.69 ± 1.14 D and −0.46 ± 1.38 D at 35◦ in the nasal and temporal degrees of visual field, respectively. Both add powers increased the relative peripheral myopic defocus up to −0.82 ± 1.23 D (p = 0.002) and −1.42 ± 1.45 D (p < 0.001) at 35◦ in the nasal field; and −0.87 ± 1.42 D (p = 0.003) and −2.00 ± 1.48 D (p < 0.001) at 35◦ in the temporal retina with +2.00 D and +3.00 D add lenses, respectively. Differences between +2.00 and +3.00 D add lenses were statistically significant beyond 20◦ in the nasal visual field and 10◦ in the temporal visual field. Conclusion: It is possible to induce significant changes in the pattern of relative peripheral refraction in the myopic direction with commercially available dominant design multifocal contact lenses. The higher add (+3.00 D) induced an significantly higher effect than the +2.00 D add lens, although an increase of 1 D in add power does not correspond to the same amount of increase in RPRE.